Stump appendicitis single centre experience: a retrospective study - Khan, Imran A.; Ramakrishnan, Parthasarathi; Subbaiah, Rajapandian; Palanisamy, Senthilnathan; Palanisamy, Nalankilli; Ganapathi, Senthil K.; Murugan, Bharath K.; Palanivelu, Chinnusamy (International Surgery Journal, 2020)
Background: Appendicectomy is the most common surgical procedure done for acute appendicitis worldwide. However, one among 50000 appendicectomy patients may present with recurrent abdominal pain, requiring hospitalization as stump appendicitis and may need completion appendicectomy. There are a few reports addressing management of stump appendicitis in the literature. Here we present our experience of laparoscopic completion appendicectomy over ten-year duration. Methods: A retrospective evaluation of records of appendicectomy from January 2008 to December 2018. All patients who had stump appendicitis as diagnosis and those who underwent completion appendicectomy were included. There were no exclusions. Details pertaining to presentation, duration of symptoms, records of previous surgery, perioperative and postoperative data was recorded, including follow-up of at least six months. Results: All 15 patients were managed by laparoscopic completion appendicectomy. Patients age range from 12 to 58 years, 12 were males and 3 female, duration of symptoms was from two to ten days, previous appendicectomy was done 4 to 84 months before, nine were diagnosed by ultrasonography of abdomen and six by CT scan, stump size ranged from 1 to 3.6 cm, mean operating time was 86.4 mins (range, 60-120 minutes). Duration of hospital stay was 3 to 5 days. There were no perioperative morbidity or mortality. Conclusions: Laparoscopic approach of completion appendicectomy is safe for management of stump appendicitis.